Efektivitas Penyaluran KUR (Kredit Usaha Rakyat) Untuk Pengembangan UMKM - Suginam Suginam; Sri Rahayu; Elvitrianim Purba (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
People's Business Credit (KUR) is a credit guarantee program, where this program is channeled to MSMEs who need additional loan funds for their businesses. After the program runs, the guarantor institution ensures that the program has been running productively or effectively so that the target for the distribution of the KUR program is achieved. The purpose of this study was to analyze the effectiveness of the distribution of People's Business Credit (KUR) and its effect on improving the performance of micro and small enterprises. The type of research used in this research is descriptive research. Descriptive research is research that seeks to describe a symptom, event, event that occurs. Descriptive research focuses on the actual problem as it was at the time the research took place. Through descriptive research, the company tries to describe events and events that are the center of attention without special treatment for these events. The last stage in data analysis is drawing conclusions and verification. The results of this study indicate that KUR can be said to be effective, because it has met the specified requirements